Good corporate governance mechanisms in moderate the relationship of earnings management and firm value: an empirical study of manufacturing firms in Indonesian - Islami, Rahmi Nur; Nursia, Nursia; Firmansyah, Sigit (Jurnal Mantik, 2024)
This research investigates the role of suitable corporate governance mechanisms in moderating the relationship between earnings management and firm value in manufacturing companies on the Indonesia Stock Exchange. This objective includes efforts to understand the extent to which good corporate governance can improve market perceptions of companies that implement earnings management, as well as providing empirical evidence about the importance of transparency and strict supervision in corporate management. In addition, this research aims to examine the influence of company size as a control variable, which can influence the relationship between earnings management and company value.The research method uses multiple linear regression analysis with moderator variables. The research results show that earnings management has a negative influence, although not significant, on company value. On the contrary, good corporate governance positively and significantly influences company value, showing the importance of transparency, accountability, and intense supervision in increasing stakeholder trust. However, the findings show that good corporate governance is insignificant in moderating the relationship between earnings management and firm value. The results of this research imply that unethical earnings management practices can harm a company's reputation in the long term. At the same time, good corporate governance positively impacts company value. Although GCG does not moderate this relationship, implementing strong GCG practices remains essential to maintain the integrity of capital markets. These results provide valuable guidance for companies and stakeholders in achieving optimal financial performance through wise earnings management and effective corporate governance.